Wizerunek życia osób starszych w oczach ich opiekunów - Wójcik, Sylwia; Brzezińska, Anna Izabela; Sienkiewicz-Wilowska, Julia Anastazja (Wydawnictwo Naukowe UAM, 2012)
In the research we look into the stereotypes caregivers hold about older people and old age and the risk factors increasing the threat of stereotypical thinking. The dominance of negative stereotypes as well as the existence of positive stereotypes distort the real image of old age and the elderly with whom carers work. Our research can be treated as a preliminary diagnosis of carers’ needs. The profi le of the group and the recognition of carers’ problems will allow for elaborating support programmes and developing an accurate educational offer. The research was conducted on 98 people working in four care homes in the Wielkopolska region. A questionnaire, based on Osgood’s semantic differential, specially drawn up for this study was used. The research demonstrates that caregivers do not treat older people in a suffi ciently individualised way. The results of cluster analysis following the k-mean procedure revealed that carers can be categorised into fi ve groups: (1) persons who do not possess suffi cient knowledge about elderly people’s needs and present common sense image of elderly people, (2) persons with realistic image about old age, (3) persons who idealise old age, (4) persons who demonise old age, and (5) persons characterized by ambivalent stereotypisation. In general, strong stereotypes were noted, both positive and negative in character. The results show that a need exists to start a discussion about the educational offer targeted at not only young people training for the profession of carers but also long-time workers of care homes looking after seniors. There is a burning need to develop more individualized educational programmes whose starting point would be a diagnosis of carers’ personal and social resources.
Elderly people image among their caregivers
Keywords: agism; attitudes; caregivers; negative stereotypes; positive stereotypes; personal and